PRÓBY PRZEDZIERANIA SIĘ DROGĄ MORSKĄ PRZEZ NIEMIECKĄ BLOKADĘ POLSKIEGO WYBRZEŻA 1 IX 2 X 1939 ROKU - Sykut, Piotr (Saeculum Christianum. Pismo Historyczne, 2017)
The article presents the attempts of Polish coast defenders’ to get through to neutral countries by sea during military operations in September and October 1939. These efforts were made in spite of the German blockade of Polish coast by Kriegsmarine ships and Luftwaffe planes. This subject hasn’t been widely featured yet using the reports of coast defenders kept in Polish and foreign archives. The goal of this article is the systematization of knowledge about these facts, presentation of characters of sailors, soldiers and civilians, who didn’t want to go into captivity. Some of them were going to continue their struggle in Polish Armed Forces in the West.